El Sermo Vulgaris frente a la Romana ungua de Lorenzo Valla (e. 1407-1457) en el Apólogo 1 contra Poggio Bracciolini (1380-1459) - Bonmatí Sánchez, Virginia (Cuadernos de Filología Clásica. Estudios Latinos, 2004)
The polemic between two notable humanists, Poggio Bracciolini (1380-1459) and LorenzoValla (c.1407- 1457), is intensified during the perio between 1451 and 454. The influence of the Disceptatio III by Poggie Bracciolini in 1450, where he expresses his concept of the different “uses” of the sermo vulgaris, and the Orationis Invectivae. Made against the Elegantiae or Romana linguo by Lorenzo Valla, become commendable N the Apologues II and I by the Elegantiae’ s author. In this latter scenic dialog, which is the subject of our study, Valla would bitingly try to blame Poggio Bracciolini for writing by using an incorrect Latin, placing him at the same level of the sermo vulgaris or vocabulum culinarium spoken by his cook or his stableman, The falseness of these accusations would be defended by Poggio in his Quinta Invectiva.